The post-bubble US economy : - Arestis, Philip (Palgrave Macmillan, 2004)
The US is slowly recovering from the aftermath of the burst of the "new economy" bubble--which was one of the worst in monetary history. Philip Arestis and Elias Karakitsos examine the causes and consequences of the burst of the "new economy" bubble and investigate the impact on financial markets. The risks and long-term prospects for the economy and financial markets are also examined.